New digestive symbiosis in the hydrothermal vent amphipoda Ventiella sulfuris - Corbari, L; Durand, L; Cambon-Bonavita, M -A; Gaill, F; Compère, P (Comptes Rendus Biologies, 2012)
Ventiella sulfuris Barnard and Ingram, 1990 is the most abundant amphipod species inhabiting the Eastern Pacific Rise (EPR 9°N) vent fields. This vent-endemic species is frequently encountered near colonies of Pompeii worms Alvinella pompejana. V. sulfuris specimens were collected during the oceanographic cruise LADDER II at the Bio9 (9°50.3′ N, 2508 m depth) hydrothermal vent site. Main objectives were to highlight the occurrence of bacterial symbiosis in V. sulfuris and to hypothesise their implications in nutrition. Observations in light and electron microscopy (SEM, TEM) showed that the outer body surface and appendages are free of microorganisms. In contrast, the digestive system revealed two major microbial communities settled in the midgut and in the hindgut. Gut contents showed bacterial traces together with abundant fragments of Alvinellid cuticle and setae, from A. pompejana, suggesting that V. sulfuris could directly feed on Alvinellids and/or on their bacterial epibionts. Molecular analyses based on the 16S rRNA genes revealed the diversity of bacterial communities in the digestive system, of which, the Epsilonproteobacteria phylum, could be considered as one of the major bacterial group. Hypotheses were proposed on their symbiotic features and their implications in V. sulfuris nutrition.
Keywords: HOV Alvin (Human Occupied Vehicle)